Resistance in germplasm of Coffea to bacterial blight incited by Pseudomonas garcae AMARAL et al - Mohan, S. K.; Cardoso, Rogério M.L.; Paiva, Marcos A. (Pesquisa Agropecuaria Brasileira, 2014)
The coffee germplasm, consisting of commercial cultivars, lines and progenies resistant to rust, varieties of Coffea arabica, C. canephora, interspecific crosses of C. Arabica x C. canephora, C. eugenioides and C. stenophylla, was evaluated in green house against the bacterial blight incited by Pseudomonas garcae (AMARAL et al) Also, the C. arabica introductions of Ethioplan origin were evaluated in the field. All the commercial cultivars - Mundo Novo, Catuaí and Bourbon - were highly susceptible. Within the rust resistant material, the progenies EP95-1520 C133, EP24-1168-18 C590, 7002-H6963 C328 were found to be resistant and M7846 to be highly resistant to bacterial blight. Among the varieties, Coffea arabica var. semierecta, C. arabica var. ennarea, and C. arabica var. geisha were imune or highly resistant. Within C. canephora two moderately resistant sources were found - Guarini LC1598-14, and Robusta 1598-11-EP119. Among the interspecific hybrids of C. arabica x C. canephora the progeny Icatu H4782-7 MBR (E) was moderately resistant. Among the progenies of the cross Timor Hybrid with Caturra, (F3) P1 34 was resistant and (F3) P1 44 was moderately resistant. One progeny of the Timor Hybrid with Blue Mountain, (F2) P1 50 showed immunity. The two species C. eugenioides and C. stenophylla also were highly resistant. Among the 138 introductions of C. arabica of Ethiopian collection, 38 sources of high resistance were identified.